Study on structure and performance of Bi–B–Zn sealing glass encapsulated Fiber Bragg Grating. (1st May 2023) - Wang, Zhenyong; Yang, Chenqian; Li, Shuangshuang; Sun, Yinghu; Ma, Qiqi; Wang, Ruohui; Wang, Hanying; Wang, Gang; Ma, Shenghua
Abstract: This article investigated the structure and packaging features of Bi–B–Zn sealing glass with Bi2 O3 concentrations ranging from 38 to 63 (wt %). The results indicate that when Bi2 O3 and the Bi/B ratio grow, the glass transition temperature (Tg) and the glass softening temperature changes correspondingly, with the lowest values occurring when the Bi/B ratio is 4. Both the infrared and Raman spectra demonstrate that the [BiO] units and [BO] units in the glass network structure increase or decrease when the Bi/B ratio increases. This modification will lower the number of broken bonds during the transition and crystallization process, hence increasing the stability of the oxide glass. The polyimide optical fiber etched with Fiber Bragg Grating (FBG) was encapsulated on 65-manganese steel, an elastic material. The results indicate that the residual pre-stress before and after encapsulation reaches 1.4 nm when the Bi/B ratio is 4 and that the encapsulation performance is commensurate with the material structure analysis results. A good glass penetration distance helps the bonding effect of the sealing glass, as seen by the microstructure of the bonding interface. At ambient temperature, the average tensile force of a G04 sample bonded with optical fiber was 2.72 N. The samples were then placed in a tube furnace replicating a high-temperature subterranean environment for an extended duration. According to the findings, the FBG sensor is capable of stable sensing.